Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Kepuasan Pelanggan dengan Keputusan Pembelian sebagai Variabel Mediasi: Studi pada Konsumen Alfamart Wilayah Singosari - Muhammad Bagas Pradana; Adya Hermawati; Survival Survival (Jurnal Manajemen Bisnis Era Digital, 2025)
This study aims to empirically analyze the influence of product quality and service quality on customer satisfaction, with purchase decisions as a mediating variable, specifically among Alfamart consumers in the Singosari area, Malang Regency. The background of this research stems from the increasing competition in the modern retail sector, which requires companies to understand the key factors influencing customer satisfaction and loyalty. In this context, product quality and service quality are considered essential elements that shape customer perceptions and influence their purchasing decisions. A quantitative approach with an explanatory research design was used in this study. The sample was selected using purposive sampling, involving 97 respondents who had made purchases at Alfamart at least twice within the last three months. Data collection was conducted through the distribution of structured questionnaires, which included items measuring perceptions of product quality, service quality, purchase decisions, and customer satisfaction. The data were analyzed using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method to examine the relationships among variables comprehensively and simultaneously. The results of the analysis show that both product quality and service quality have a significant and positive effect on purchase decisions and customer satisfaction. Moreover, purchase decisions are proven to significantly mediate the influence of both product and service quality on customer satisfaction. This indicates that the purchase decision acts as a crucial mechanism linking the effect of quality to overall satisfaction. These findings contribute theoretically to the consumer behavior literature in the modern retail context and offer practical implications for retail management, such as Alfamart. Retailers are encouraged to focus on improving both product offerings and service delivery as strategic efforts to enhance customer experience. By doing so, they can effectively increase customer satisfaction and strengthen customer loyalty in the long term.